التنامي الدلالي الجمالي لأدوات قراءة القصيدة المعاصرة: دراسة تنظيرية تطبيقية - د. هالة أبا يزيد بسطان محمد (White Nile Journal for Studies and Research, 2022)
This study attempted to present some of the techniques of poetic readings, which are concerned with unraveling the syntactic connotations, whether expressive or figurative. This is done through two axes: the first: the growth of the critical reading term for the contemporary poem, and the second: the aesthetic semantic keys to reading the contemporary poem. The study was issued with an introduction explaining some of the terms attached to the title: (development, reading, and contemporary). The study will take, in its pivots, the Diwan: "Kazour Al-Gamama fi Al-Naba" by the poet Osama Taj Al-Sir Ahmed as a model for some aspects of reading, as evidence and representation, through choices from the bellies of the poems or from their preambles; Due to the abounding in the Diwan of aesthetics related to the contemporary poem and the growing artistic generation semantic. The presentation method will be the descriptive and inductive method. The study concluded to prove the steady growth of critical reading tools according to the growth of the poem itself, an artistic, semantic and aesthetic development